ROLE OF LECTURERS AS A JOURNALISM EDUCATOR - Diyah Yuli Sugiarti (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2019)
The purpose of this research is to determine the role of lecturers as journalism educator. This research uses quantitative approach. Data was taken from the literature analysis, observations and interviews to lecturers at Islamic University